BANK COMPETITION AND RISK-TAKING IN THE EUROPEAN UNION: EVIDENCE OF A NON-LINEAR RELATIONSHIP - Căpraru, Bogdan; Ihnatov, Iulian; Pintilie, Nicoleta-Livia (Economic Annals, 2021)
This paper assesses the impact of bank specialisation and business models on the relationship between competition and risk. We tested the non-linear relationship between bank competition and risk on an extensive sample of 5,119 European banks active during 2000–2018, using system GMM. The results confirmed the nonlinear relationship between competition and risk-taking. Cooperatives are better protected against liquidity risks and are more stable. Well-diversified banking entities take more risks than their counterparts, whereas larger institutions have a lower risk appetite and a higher exposure to liquidity shocks. Future regulations should consider different risk strategies to make them more efficient and to generate the expected outcomes. The most recent regulatory developments have reduced the risk appetite of large financial institutions. Lastly, it is critical that regulators monitor M&A activity and ensure the optimal competition level.